2021
DOI: 10.3390/rs13173538
|View full text |Cite
|
Sign up to set email alerts
|

Deriving Aerodynamic Roughness Length at Ultra-High Resolution in Agricultural Areas Using UAV-Borne LiDAR

Abstract: The aerodynamic roughness length (Z0) and surface geometry at ultra-high resolution in precision agriculture and agroforestry have substantial potential to improve aerodynamic process modeling for sustainable farming practices and recreational activities. We explored the potential of unmanned aerial vehicle (UAV)-borne LiDAR systems to provide Z0 maps with the level of spatiotemporal resolution demanded by precision agriculture by generating the 3D structure of vegetated surfaces and linking the derived geomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…where x = [1-19z m /L] 1/4 ; L(m) and T * (K), respectively, are the Monin-Obukhov rough length and friction temperature, which can be calculated from Equations ( 5) and (6). The screening wind speed is greater than 1 m/s; the friction speed is greater than 0.01 m/s; the sensible heat flux is greater than 10 W/m 2 ; no rain; the acquisition time is daytime flux data.…”
Section: Aerodynamic Roughnessmentioning
confidence: 99%
See 1 more Smart Citation
“…where x = [1-19z m /L] 1/4 ; L(m) and T * (K), respectively, are the Monin-Obukhov rough length and friction temperature, which can be calculated from Equations ( 5) and (6). The screening wind speed is greater than 1 m/s; the friction speed is greater than 0.01 m/s; the sensible heat flux is greater than 10 W/m 2 ; no rain; the acquisition time is daytime flux data.…”
Section: Aerodynamic Roughnessmentioning
confidence: 99%
“…A large number of studies have been carried out on the surface parameters, atmospheric boundary layer, and stability of each underlying surface in the arid and semi-arid zone [4], and Peng et al [5] combined machine learning techniques, wind profile equations, station observations, and MODIS remote sensing data to estimate the daily dynamic roughness on a global scale. Trepekli et al [6] used a UAV-mounted lidar system to estimate the dynamic roughness of the underlying surface under farmland. Ma et al [7] evaluated a variety of thermodynamic roughness schemes, and the results showed that the C97 scheme had the best effect on the underlying surface in the grassland of eastern Tibet.…”
Section: Introductionmentioning
confidence: 99%
“…2021 generated a dataset of global aerodynamic parameters for the period 1982 to 2017, employing remote sensing measurements of Leaf Area Index (LAI), canopy height, and canopy morphological characteristics, with the canopy height estimated through a semi-empirical approach based on LAI. More recently, ultra-fine resolution (0.1 m) spatial maps of 𝑧 0 have been developed from LiDAR systems mounted on Unmanned Aerial Vehicles (Trepekli and Friborg 2021). Overall, it can be summarized that remote sensing / satellite-based methods for estimating roughness parameters are becoming more reliable and popular in recent years.…”
Section: Introductionmentioning
confidence: 99%